Responsibility of Notary for Registered Private Deed in the Perspective of Law of Evidence - Bayu Indra Permana; Mohammad Rafi Al Farizy; Ferdiansyah Putra Manggala (Universitas Muhammadiyah Gresik, 2024)
In public life, there is a relationship between one party and another which will involve rights and obligations, which will lead to many violations, one of which is a legal event. Notary is a public official who is appointed by the government to assist the community in terms of an agreement, the only one with an authentic deed. The task of the notary is not only to make an authentic deed but also to register and validate the letter under the hand or called waarmeken. In the aspect of proof in court, the letter under hand that has been guarded does not have perfect evidentiary power because it lies in a signature which, if acknowledged, then the deed will become perfect evidence such as an authentic deed.